151k views
4 votes
-5-(-11)-(-11).
what’s the answer

User AnoE
by
5.3k points

2 Answers

3 votes

Answer:


\Large \boxed{17}

Explanation:

-5-(-11)-(-11)

=17

This is one way to do this;

1. => (-5−-11)−(0−11)

=> 6−(0−11)

=>6−-11

=17

Another way to do this;

First remove the parentheses.

-5+11+11

And than simplify.

6+11

=17

Answer;17

User Greg Blass
by
5.1k points
2 votes

Answer:
17

Subtract


-5-(-11)=6

Subtract


6-(-11)=17

User Vinit Dabhi
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.